Ebony magazine and Lerone Bennett Jr. : popular black history in postwar America - West, E. James (University of Illinois Press, 2020)
"This study reveals the previously hidden impact of Ebony magazine as a major producer and disseminator of popular black history during the second half of the twentieth century. Far from dismissing Ebony as a consumer magazine with limited political or educational importance, E. James West highlights the value editors, readers, and advertisers placed upon Ebony's role as a "history book." Benefiting from unprecedented access to new archives at Chicago State and Emory University, West also offers the first substantive biographical account of the writing and philosophy of Lerone Bennett Jr., who used his position at Ebony to emerge as one of the twentieth century's most influential popular black historians. Focusing on Lerone Bennett's role within Johnson Publishing, and assessing Ebony's broader historical coverage, this book uses the magazine as a window into the transition of black history from the margins to the center of American cultural, historical, and political representation. As an important cultural outlet with millions of readers, Ebony played a powerful role in reshaping public representations of African American history. Directed by the efforts of Bennett, the magazine produced militant depictions of black history and connected activism in the present to a longstanding history of radical black protest. However, as a black consumer magazine it also helped to legitimize and facilitate corporate mediation of black history, and to frame and limit discussions of African American history, memory, and identity"-- Provided by publisher
Keywords: Bennett, Lerone, -- Jr., -- 1928-2018.; Ebony (Chicago, Ill.) -- History.; Bennett, Lerone, -- Jr., -- 1928-2018; Ebony (Chicago, Ill.); Journalists -- United States -- Biography.; African American journalists -- Biography.; Historians -- United States -- Biography.; African American historians -- Biography.; Journalistes -- États-Unis -- Biographies.; Journalistes noirs américains -- Biographies.; Historiens -- États-Unis -- Biographies.; Historiens noirs américains -- Biographies.; HISTORY -- General.; African American historians; African American journalists; Historians; Journalists; United States; Electronic books.; Biography; Biographies; History; Biographies.